DEX‐2‐TKA—DEXamethasone twice for pain treatment after Total Knee Arthroplasty: A protocol for a randomized, blinded, three‐group multicentre clinical trial. Issue 2 (18th October 2019) - Gasbjerg, Kasper S.; Hägi‐Pedersen, Daniel; Lunn, Troels H.; Jakobsen, Janus C.; Overgaard, Søren; Pedersen, Niels A.; Bagger, Jens; Lindholm, Peter; Brorson, Stig; Schrøder, Henrik M.; Thybo, Kasper H.; Mathiesen, Ole
Abstract : Background: Multimodal analgesia is considered the leading principle for post‐operative pain treatment, but no gold standard after total knee arthroplasty (TKA) exists. Aim: To investigate the beneficial and harmful effects of one or two doses of 24 mg intravenous dexamethasone (DXM) as part of a multimodal analgesic regimen (paracetamol, NSAID and perioperative local infiltration analgesia) after TKA. We hypothesize that addition of DXM will reduce post‐operative opioid consumption. Methods: DEXamethasone twice for pain treatment after TKA is a randomized, blinded, three‐group multicentre clinical trial. Participants will be randomized to one of three groups: placebo, single dose of DXM or two consecutive doses of DXM. Participants, treatment providers and investigators will be blinded to the allocated intervention. The primary outcome is total opioid consumption (units of morphine equivalents) 0‐48 hours post‐operatively. Inclusion criteria: unilateral, primary TKA; age ≥18 years; American Society of Anesthesiologists‐Score 1‐3; Body Mass Index ≥18 and ≤40; for women—not pregnant; and written informed consent. Exclusion criteria: allergy or contraindications against trial medication; daily use of high dose opioid and/or use of methadone/transdermal opioids; daily use of systemic glucocorticoids; dysregulated diabetes; and patients suffering from alcohol and/or drug abuse. Four‐hundred‐and‐eighty‐six eligible participants are needed to detect or discard a difference of 10 mg morphine equivalents 0‐48 hours post‐operatively maintaining a familywise error rate of 0.05 and a power of 90% for the three possible pairwise comparisons. Discussion: Recruiting is planned to commence September 2018 and expected to finish March 2020. Trial Registration: EudraCT: 2018‐001099‐39 (08/06‐18); ClinicalTrials.gov: NCT03506789 (24/04‐2019). Editorial Comment This is the protocol for the largest randomized clinical trial investigating the effect of one or two doses of dexamethasones on pain treatment after total knee arthroplasty. Due to the pragmatic and rigerous design this study will deliver results of high quality and external validity.